Velikost legla, velikost jajc in fenologija prihoda na gnezdišče pri navadni čigri Sterna hirundo v SV Sloveniji - Janžekovič, Franc (Acrocephalus, 2003)
Common Terns Sterna hirundo began to return to their breeding sites on the Drava river in early April. The article presents the measurement of 471 Common Terns' eggs from 184 nests. Average clutch size was 2.55 (median = 3, min = 1, max = 4) eggs per nest, with an average egg size of 41.1 x 30.3 mm. There was no characteristic difference in the average egg length between the two-, three- and four-egg clutches. Concerning the average breadth of eggs, characteristic differences were noted particularly in four-egg clutches. Correlation between egg length and breadth was very loose (r = 0.25, p 0.0001). Egg length was more variable (CV%EL =4.33) than egg breadth (CV%EB = 2.96). Size patterns in Common Terns' clutches were not quite consistent with the brood-reduction hypothesis, according to which every egg laid in a single nest is smaller than the previous one
Keywords: bird; ptice; čigre; navadna čigra; Slovenia; Slovenija